2018
DOI: 10.1007/s11223-018-9948-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural Strength and Service Life of the Extrusion Forming Die for Agricultural Engine Piston Heads

Abstract: Three-tier high-strength prestressed combination concave dies are designed to manifacture highpower corn combine harvester engine piston heads. This design integrates the advantages of traditional casting or hot die forging and warm extrusion. The following key parameters, viz radial dimensions of each mating layer, axial bonding and radial contact interaction, are obtained by theoretical calculation. Nonlinear analysis of the contact interaction was carried out, and the die contact condition was studied at no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…And the element strain {ε} e and stress {σ} e can be calculated from element nodal displacement using {u} e Eqs. (16) and (17), respectively.…”
Section: Static Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…And the element strain {ε} e and stress {σ} e can be calculated from element nodal displacement using {u} e Eqs. (16) and (17), respectively.…”
Section: Static Structural Analysismentioning
confidence: 99%
“…Pedersen [15] performed the fully coupled fluid-solid analyses together with self-developed elastic-plastic material behaviour to study the low cycle fatigue of the forward extrusion dies. The univariate linear regression equation of the service life of extrusion forming die was derived by Yang et al after conducting the numerical simulation of the die wear in each operation cycle [16]. In addition, Lin et al [17] have optimized the geometry to improve the service life of hot extrusion dies using FE analysis and updated sequential quadratic programming (SQP) method.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [13] described the salt fog corrosion law of the sprocket of 40Cr steel under extrusion forming temperatures of 550 , 650 , and 750 . Yang [14] evaluated the structural strength and service life of hot extrusion die through a numerical simulation of mold wear in each working cycle. Torkian [15] showed the effect of multi-and sub-channel angular temperature extrusion on the mechanical properties of WE43 magnesium alloy and found that the hardness increases with the channel number.…”
Section: State Of the Artmentioning
confidence: 99%
“…Torkian [15] showed the effect of multi-and sub-channel angular temperature extrusion on the mechanical properties of WE43 magnesium alloy and found that the hardness increases with the channel number. Liu [13], Yang [14], and Torkian [15] analyzed the corrosion, strength life, and hardness of the warm extrusion forming method only from a single examination target, respectively.…”
Section: State Of the Artmentioning
confidence: 99%